Design, implementation, and evaluation of a CPOE system in a cancer care setting: A case study on the gastric cancer patients - Mohammad Reza Afrash; Shirin Kianersi; Mohammadkarim Bahadori (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Chemotherapy is a complex, multi-disciplinary, and error-prone process. Information technology is being increasingly used in different health care settings with complex work procedures such as cancer care to enhance the quality and safety of care. In this study, we aimed to develop a computerized physician order entry (CPOE) for chemotherapy prescribing in patients with gastric cancer and to evaluate the impact of CPOE on medication errors and order problems. MATERIALS AND METHODS: A multi-disciplinary team consisting of a chemotherapy council group and system design and implementation team was formed for chemotherapy process evaluation, requirement analysis, developing computer-based protocols, and implementation of CPOE. A before and after study was conducted to evaluate the impact of CPOE on the chemotherapy process and medication errors and problem orders. To evaluate the level of end-user satisfaction, an ISO Norm 9241/110 usability questionnaire was chosen for the evaluation. RESULTS: Before the implementation of the CPOE system, 37 medication errors (46.25%) and 53 problem orders (66.25%) were recorded for 80 paper-based chemotherapy prescriptions. After implementation of the CPOE system, 7 (8.7%) medication errors and 6 (7.5%) problem orders were recorded for 80 CPOE prescriptions. The implementation of CPOE reduced the medication error by 37.55% and the problematic order by 58.75%. The results for usability evaluation indicate that the CPOE was within the first class of the ISONORM level rating; this shows that a CPOE is with very high satisfaction and a very high functionality rate. CONCLUSION: Developing a CPOE system significantly improved safety and quality of the chemotherapy process in cancer care settings by reducing the medication error, deleting unnecessary steps, improving communication and coordination between providers, and use of updated evidence-based medicine in direct chemotherapy orders. However, the CPOE system does not prevent all medication errors and may cause new errors. These errors can be human-related factors or associated with the design and implementation of the systems.